2021
DOI: 10.1007/978-3-030-90033-5_18
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of Residential Energy Consumption Accounting for Occupant-Behavior and Building Characteristics: A Coupled Statistical Approach with Reduced Survey and Simulation Tool

Abstract: According to the International Energy Agency, occupant Behavior is among the six driving factors of energy uses in Buildings. Therefore, it is widely considered a great influence on energy performance and must be studied concerning the influencing parameters, such as: Indoor and outdoor environmental quality, personal, cultural, and physiological factors; also, physical and structural conditions of the building should be included. However, the literature's studies show that this analysis is not frequently perf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…2. For the thirty-eight houses, an average of 1.90 kWh/m 2 /month was found per house (or 6.0 kWh/m 2 /month) in primary energy terms [89] without considering gas consumption. 4.…”
Section: Tablementioning
confidence: 99%
“…2. For the thirty-eight houses, an average of 1.90 kWh/m 2 /month was found per house (or 6.0 kWh/m 2 /month) in primary energy terms [89] without considering gas consumption. 4.…”
Section: Tablementioning
confidence: 99%
“…The factors considered were the number of occupants (X1), air conditioning (AC) (X2), light bulbs (X3), fans (X4), areas of the house (X5), floor area (X6), age of occupants (X7), thermostat adjustment (X10). This section seeks to find the behavior of energy consumption depending on the occupant's preferences as far as the use of appliances is concerned [27].…”
Section: Typical Occupant Behavior Estimation For the Case Studymentioning
confidence: 99%
“…Due split units don't provide an air change rate, this may have an impact over IAQ, in other words, rising pollutant concentration. González et al [11] discovered by employing a survey analysis to know occupants' preferences that most participants in the study, selected split air units as their cooling systems, thus it's the most common and known mechanical ventilation system utilized. In contrast, [12] showed that occupants of buildings with centralized ventilations system were thermically unsatisfied compared to occupants who worked in spaces with split units, since with this type of ventilation, the user can control the interior temperature at his comfort.…”
Section: Introductionmentioning
confidence: 99%